Post-traumatic stress disorder symptoms and associated factors in breast cancer patients during the first COVID-19 lockdown in France - Yahi, Feriel; Lequesne, Justine; Rigal, Olivier; Morel, Adeline; Leheurteur, Marianne; Grellard, Jean-Michel; Leconte, Alexandra; Clarisse, Bénédicte; Joly, Florence; Lefèvre-Arbogast, Sophie (Frontiers in Psychology, 2022)
Introduction: We aimed to study post-traumatic stress disorder (PTSD) symptoms in breast cancer patients during the coronavirus disease (COVID-19) pandemic. Methods: We included breast cancer patients receiving medical treatment during the first COVID-19 lockdown in France. PTSD symptoms were evaluated using the Impact of Event Scale-Revised (IES-R) questionnaire. Quality of life (FACT-G), cognitive complaints (FACT-COG), insomnia (ISI), and psychosocial experiences during lockdown were also evaluated. Multivariable logistic regression was used to identify clinical factors (from medical records) and psychosocial factors (from questionnaires) associated with PTSD symptoms. Results: Among the 253 included breast cancer patients (mean age: 58), 46% had metastatic cancer and 52% were treated by chemotherapy alone. COVID-19-induced adjustments in medical oncology practices were experienced by 27% of patients (mainly teleconsultations). No case of COVID-19 was reported. 23% of breast cancer patients had PTSD symptoms. Compared to other patients, patients with PTSD symptoms had more fears relative to COVID-19 infection (83% vs 60%, p=0.009), had more feeling of isolation (69% vs 41%, p=0.003), and more prescription or increased use of psychotropic drugs (49% vs 20%, p=0.001). In the multivariable model adjusted for clinical factors, fears relative to COVID-19 and increased use of psychotropic drugs were independently associated with PTSD symptoms (OR [95% CI] = 3.01 [1.20-8.44] and 3.45 [1.48-8.17] respectively). Besides, patients with PTSD symptoms had poor quality of life, and more cognitive complaints and insomnia. Conclusion: PTSD symptoms were observed in 23% of breast cancer patients during the first COVID-19 lockdown in France. Psychological supports are needed for patients treated during the COVID-19 pandemic.